Temporal trends in antimicrobial resistance of medically important pathogens on Curaçao - Peter M. C. Klein Klouwenberg; Claudy Oliveira dos Santos; Diederik van de Wetering; Lisette Provacia (Antimicrobial Resistance and Infection Control, 2024)
Abstract Background The Caribbean lacks recent comprehensive antimicrobial resistance data to inform clinicians and decision-makers. This study aims to provide a snapshot of susceptibility trends for pathogens on Curaçao, an island in the southern Caribbean. Methods We analyzed susceptibility data of bacterial pathogens isolated from samples submitted from patients attending general practitioners, outpatient clinics and those who were hospitalized between January 2018 and December 2023. Samples originating from blood, urine, genital tract, soft tissue, and lungs were included. Susceptibility testing was performed by VITEK2 according using the European Committee on Antimicrobial Susceptibility Testing criteria. Results In total, 13,528 patients contributed to 22,876 first isolates. Of all infections in adults with Staphylococcus aureus, 14% (95% confidence interval 10–18%) were methicillin-resistant S. aureus (MRSA) in blood, and up to 27% (20–35%) in soft-tissue cultures. For Escherichia coli and Klebsiella pneumoniae, resistance levels were up to 27% (95% CI 22–32%) for cefuroxime and up to 18% (95% CI 18–28%) for third-generation cephalosporins. The addition of gentamicin to empirical therapy with cefuroxime increased coverage only moderately, especially in K. pneumoniae (16%, 95% CI 12–20%). Resistance to amoxicillin-clavulanic acid was up to 47% (95% CI 43–50%), to ciprofloxacin 34% (95% CI 31–37%) and to cotrimoxazole 37% (95% CI 34–39) in urine cultures from outpatients. In contrast, low levels of carbapenem resistant Enterobacterales and Pseudomonas aeruginosa were observed. Conclusions Antimicrobial resistance is high and widespread across several important antibiotic classes. The widespread occurrence of MRSA and resistance to third-generation cephalosporins highlights the importance of identifying risk factors, enabling more effective guidance for antimicrobial stewardship.